Numerical Time-Domain Modeling of Lamb Wave Propagation Using Elastodynamic Finite Integration Technique - Hussein Rappel; Aghil Yousefi-Koma; Jalil Jamali; Ako Bahari (Shock and Vibration)
This paper presents a numerical model of lamb wave propagation in a homogenous steel plate using elastodynamic finite integration technique (EFIT) as well as its validation with analytical results. Lamb wave method is a long range inspection technique which is considered to have unique future in the field of structural health monitoring. One of the main problems facing the lamb wave method is how to choose the most appropriate frequency to generate the waves for adequate transmission capable of properly propagating in the material, interfering with defects/damages, and being received in good conditions. Modern simulation tools based on numerical methods such as finite integration technique (FIT), finite element method (FEM), and boundary element method (BEM) may be used for modeling. In this paper, two sets of simulation are performed. In the first set, group velocities of lamb wave in a steel plate are obtained numerically. Results are then compared with analytical results to validate the simulation. In the second set, EFIT is employed to study fundamental symmetric mode interaction with a surface braking defect.